Use of artificial water troughs by deer in the Maya forest, México - Contreras-Moreno, Fernando M.; Jesús-Espinosa, Daniel; Sánchez, Khiavett; Méndez-Tun, José; Cruz-Romo, Lizardo (THERYA, 2024)
Artificial water troughs have been implemented in the Calakmul region as a measure that contributes to the maintenance of wildlife populations during the drought season. The aim of this study was to estimate the use of artificial water troughs by three species of deer (Odocoileus virginianus, M. pandora, and Mazama temama) in the Maya Forest of Campeche in southeastern México. The study was carried out in the Calakmul Biosphere Reserve (CBR, in Spanish) in southeastern México. Seventy artificial water troughs were installed, most of them within the core areas of the CBR. Between December 2018 and August 2021, eight digital traps were placed in eight artificial water troughs to monitor the presence of deer. The Photographic Visit Index (PVI) was calculated, and the visit rates of each species were compared by sampling year for each monitoring station. Deer activity patterns were evaluated using circular statistics to assess whether there were differences between visiting times. Watson-Williams tests were performed during the different sampling months. The density of records was analyzed to identify the degree of overlap in the deer activity patterns. With a sampling effort of 4,672 nights/camera, we captured 477 records of O. virginianus, 229 of M. pandora, and three of M. temama using artificial water troughs in the CBR. Due to the scarce records of M. temama in water troughs, comparative analyses were performed only with the other two deer species. According to the PVI, in the case of O. virginianus, highly significant differences were found between the three sampling years (H = 12.575, df = 2, P < 0.001); similarly, M. pandora showed highly significant differences between sampling years (H = 9.29, df = 2, P = 0.001). Regarding activity patterns, O. virginianus is mainly diurnal, with peaks of activity in the early hours of the day (8:00 h to 9:00 h). M. pandora was also mainly diurnal, showing the highest peaks of activity in the early hours of the day and before dusk. O. virginianus and M. pandora regularly visit water troughs, and the presence of deer in water troughs responds to their need to drink water for thermoregulation. The activity pattern of deer was mainly diurnal; it is safer for both species to move during the day because predators were recorded constantly in the study area. The degree of overlap recorded between O. virginianus and M. pandora suggests that both species are active at the same times of the day.